The Role of FinTech and Institutional Quality in Enhancing Economic Readiness amid Climate Risks - Sudarwati; Hendra Titisari, Kartika (Inovasi Analisis Data, 2025)
Purpose: We explore how institutions’s adaptability, FinTech and business age dynamics intersect in the emergence of economic readiness for climate adaption across a range of national contexts.Method: Based on panel data analysis of 80 countries over a span of ten years, this study utilizes fixed effects regression; moderation analysis using SPSS Macro; quantile regression; and robustness checks, including lagged variables and panel-corrected standard errors, to confirm the robustness of the results.Findings: FinTech has a significantly positive influence on economic preparedness, and this influence is moderated by institutional quality and firm development stage. Digital financial innovations have a deeper impact on countries with more dynamic institutions and structurally more developed business environments. Quantile regression shows that such an effect becomes more pronounced in relatively high-achieving economies, while regional analysis demonstrates that advanced economies make better use of FinTech than developing economies.Novelty: Laying out the contextual conditions under which FinTech can create economic resilience, this study serves to connect digital finance and sustainability. Contrary to earlier works which examine only the technological and economic aspects, this study included institutional and business structure factors in the nexus between FinTech and readiness to adopt it.Implications: The results show that there is no one-size-fits-all approach to FinTech by policymakers and diverse international development organisations. Instead, investments in institutional reforms and business development are critical in unleashing the full potential of FinTech in climate preparedness efforts.